Relationship Between Hemoglobin Level and Feeding Pattern in Apparently Healthy Children Below Two Years - Ahmed, Ahmed A.; Al-Rabaty, Abbas A.; Alnakshabandi, Abdulkadir A. (Zanco Journal of Medical Sciences (ZJMS), 2010)
Background and objective: Anemia is still one of the most common problems in the world even in developed countries, but its evaluation is still underestimated especially in developing countries like our, so it needs further planning, screening and management. This study was done in 12 primary health care centers PHCC in Erbil city – Kurdistan re-gion/Iraq during period fro 1st Feb - 31st Jul 2008. The main objectives were to determine the hemoglobin value in our children , to estimate the prevalence of anemia and correlating it with feeding pattern . Methods: This prospective study was conducted in 500 apparently healthy children col-lected randomly, visiting the vaccination centers routinely during 5 months period. Feeding. pattern were studied in relation to hemoglobin (Hb) level only. Results: From total 500 children conducted in this study, the mean Hb. of them was 10.4 g/dl. Those with normal Hb were 196 (39.2%), while 304 (60.4%) of them were anemic. Those with mild anemia were 145 (29.0%) and 159 (31.8%) of them had moderate anemia. The sex had no effect on Hb level. The anemia was lesser in children below one year Children on breast feeding had lower percent of anemia (51.9%),those on exclusive breast feeding only 6 (33.4%) while those on adult milk (74.9%) of them were anemic. Conclusion: There was a high prevalence of anemia among the investigated children and less common in children with breast feedin. .